'You come because it is an interesting place': The impact of attending a heritage programme on the well-being of people living with dementia and their care partners. (August 2021) - Innes, Anthea; Scholar, Helen F; Haragalova, Jana; Sharma, Monika
Promoting access to heritage settings has been acknowledged as a way to promote well-being in the United Kingdom for people living with dementia and their care partners. Yet there is a lack of information available internationally on the contribution of heritage sites to promote well-being and social inclusion for those living with dementia. This study addresses this gap by reporting on the impact for 48 people of participating in the 'Sensory Palaces' (SP) programme run by Historic Royal Palaces at Hampton Court and Kew Palaces in the United Kingdom. Two primary data sources were used; post-session interviews involving 30 participants (the person living with dementia and/or their care partners), and 131 sets of self-complete pre- and post-session mood questionnaires administered directly before and after SP session attendance. Analysis of the data sets is presented under three themes: enjoyment and engagement; connecting and learning and place, space and time. The findings demonstrate that participants highly valued the heritage sessions and reported positively on the impact this had for their individual well-being and their relationships with one another. This study highlights the opportunity for heritage sites to contribute to promoting well-being for people living with dementia.